Development of a Community-Based Marine Tourism Attraction in the Samboang Beach in Bulukumba Regency - Syahrial Syahrial; Muh. Zainuddin Badollahi (Newinera Publisher, 2020)
Bonto Tiro Subdistrict is one of the areas in Bulukumba Regency which has a tourism potential that can be developed as a marine tourism attraction, one of which is the Samboang beach, where the beach has beautiful panoramic views with white sandy beaches, and the presence of coral reefs. can be used as one of the attractions, besides the underwater scenery is also reliable and is also a potential area for the development of marine tourism, this research is focused on aspects of developing tourist destinations with various components of tourism destinations in Samboang Beach, Bonto Tiro District, Bulukumba Regency. This study aims to find out how the development of tourism destinations in the Samboang beach through 4 tourism components, namely Attraction, Accessibility, Ancillary, Amenity in supporting marine tourism destinations so that they develop even more. This research is qualitative research with an observation approach, and research instruments in the form of a list of interviews, field observations and literature studies, while the theories underlying this research are tourism destination theory and tourism development theory. And from the research results obtained by researchers, it can be concluded that the development of marine tourism destinations is very supportive in developing the region as an area that has a tourist attraction.